Cidades possíveis : espaço e gênero em escolhas de mobilidade urbana - Gabriela Cicci Faria (2019)
This research focused on the criteria of choice used in urban mobility to reveal complex dynamics in articulations between gender, space and time. We aimed to identify and systematize the selection criteria used by inhabitants of Belo Horizonte in determining their urban mobility paths, making, from there, an analysis of the differences between men, women and women in different contexts. As methodology, quantitative methods of descriptive statistical analysis of the Origin-Destination Survey (2012) were used, as well as qualitative methods of interview and affective mapping. It is concluded that there are deep gender inequalities in the possibilities to be mobile and in on-the-move experiences, these being constantly crossed by particularities of class, race and place of dwelling.